(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Mineralogical analysis of Moheskhali beach sands revealed the presence of high amount of ilmenite. About 50% of these ilmenites are unaltered which are characterized by the presence of exsolution of ilmenite with hematite, ilmenite with magnetite, and ilmenite with rutile. Others (50%) are unexsolved where 30-50% grains partially or fully altered. These altered and unaltered phases of ilmenite are confirmed by X-Ray diffraction study. Ilmenite-hematite exsolution comprising 70-80% of the total exsolution. The widely banded exsolved phases were formed by continuous exsolution mechanism while the second generation thinner bands were formed discontinuously. Seriate texture dominates (about 75%) over emulsion, granular, quadrangular, sub graphic, veined and special types. Optical study suggests that the alteration of ilmenite is seen to proceed along grain boundaries and/or fractures resulting in an amorphous to microcrystalline mass resembling leucoxene. The chemical composition of the alteration products of ilmenite frequently fluctuates within definite ranges (pseudoilmenite and pseudorutile ranges) of a nonstoichiometric composition and thus deviates from their ideal composition. Key words: Ilmenite; Rutile; Opaque; Exsolution; Alteration. DOI: 10.3329/bjsir.v45i1.5173 Bangladesh J. Sci. Ind. Res. 45(1), 17-26, 2010